Analysis of the CEAS in relation to the current crisis with asylum seekers - Simonsen, Frederik (Riga Graduate School of Law, 2021)
In order for the EU to handle the migration crisis, the Common European Asylum System (CEAS) has been implemented. It is a mechanism created to deal with all the formalities in regard to admission for protection of asylum seekers in the first place, ending with making sure the asylum seekers are safe and sufficient for life in the Member State where his/her life will further continue. Although the system has thoroughly been developed and is tailored to meet all the possible requirements which would formally be needed in order to receive asylum seekers, the general experience and operation of the system in practice is often not as efficient and transparent as it should be, if one were to solely refer to the components of the CEAS. Throughout this Thesis, the author will analyse the CEAS as a solution proposed by the EU in handling the inflow of asylum seekers as a result of the Crisis in the Middle East. The findings of the analysis will further be examined to understand how useful of a solution the CEAS has been in reality and what flaws does the system have in regard to future developments that could be made to the system.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Asylum